CADMIUM AND LEAD STATUS IN CORN HYBRIDS GROWN ON ACID SOIL OF EASTERN CROATIA - V. Kovačević; I. Kadar; J. Koncz; I. Brkić; Đ. Banaj (Poljoprivreda, 2002)
Twenty corn (Zea mays L.) hybrids were grown under field conditions in the west part of Brodsko-posavska county in Eastern Croatia during 2000 and 2001 growing seasons. The field trial was conducted in four replicates. The ear-leaf at beginning of silking stage (the second decade of July) was taken for chemical analysis from each plot. Mean soil sample was taken by auger to 30 cm of depth. The total amounts of Cd and Pb in corn leaves were measured by ICP-AES technique after their microwave digestion using concentrated HNO3+H2O2. Mobile fraction of these elements in soil was extracted by ammonium acetate-EDTA solution. The experimental field is acid hydromorphic soil (locality Malino) with moderate levels of mobile fractions of calcium, magnesium and aluminum. Also, mobile fraction of cadmium and lead are tolerable for growing of health food. Weather conditions during the study differed from the long-term mean. Low rainfall quantities during 5-months period and the higher air-temperatures characterized the 2000 growing season. Excess of rainfall in June and September, their shortage in July and August, as well as high temperatures in August, are main characteristics of weather during the corn growing seasons in 2001. Mean concentrations of cadmium and lead in corn leaves in our investigations were 0.14 ppm Cd and 0.420 ppm Pb. These amounts are low and not dangerous for plants, because critical concentrations of Cd and Pb in plants ranged from 5 to 10 ppm Cd and 10-20 ppm Pb. Considerable differences of cadmium and lead status in the ear-leaf were found among tested corn hybrids. For example, genetically induced differences from 0.07 to 0.21 ppm Cd were found, while these values for Pb were from 0.241 to 0.569 ppm Pb. Especially low Cd concentrations were found in six corn hybrids (OsSK373, E9917/99, Bc278, OsSK2-191, OsSK382 and Clarica: mean 0.092 ppm Cd), while in three hybrids it was considerably higher, but acceptable from the aspect of plant and animal health (OsSK395, OsSK378 and Tvrtko 303: mean 0.200 ppm Cd). Very low Pb concentrations were found in two hybrids (Clarica and OsSK373: mean 0.268 ppm Pb), while in three hybrids they were above 0.500 ppm Pb (RK1456/99, osSK382 and Bc278: mean 0.542 ppm Pb). In general, production of healthy food based on principles of sustainable agriculture is possible under tested environmental conditions.Keywords: acid soil, cadmium, corn hybrids, lead, yield, Croatia